Pengaruh Konsentrasi Asam Cuka terhadap Sporulasi Beauveria bassiana (Bals.) Vuill Strain-Wamena pada Medium Beras Pera Sebagai Agen Hayati - Rini Patandungan; Rosye H.R. Tanjung; Mesak Kamarea (Jurusan Biologi FMIPA Universitas Cenderawasih, 2009)
This study carried out at Laboratory of Biology, Division of Food and Cultivated Plants Protection, Jayapura from January-June 2008. The objective of this study was to examine the effect of citric acid (CH3COOH) concentration on rate of growth and spore production of Beauveria bassiana (Bals.) Vuill. strain Wamena which grow in short grain rice (beras pera) media. Six different concentration of citric acid (CH3COOH) were 0; 0,025%; 0, 05%; 0,075%; 0,1% and 0,125% with 5 replicates for each concentration, complete random design were used. Result of this study showed that 0.05% of citric acid significantly affected spore production which mean potential for biological control agent. Key words: Beauveria bassiana (Bals.) Vuill Strain Wamena, rice medium, biological control agent.